A polyanionic sodium-ion battery cathode material and a preparation method thereof

CN123017954APending Publication Date: 2026-10-30SHANDONG SACRED SUN POWER SOURCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611519578.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但是聚阴离子型正极材料普遍存在电导率低的问题,使得电化学反应较慢,严重影响该材料的电化学性能,限制了其倍率性能和长循环寿命,因此,开发高性能的聚阴离子型钠离子电池正级材料至关重要

Benefits of technology

1、由于本申请在聚阴离子正极材料颗粒表面包裹二氧化钛/碳纤维复合层,通过酸化碳纳米纤维粉末在颗粒间相互连接,形成长程、连续的三维导电骨架,为电子提供快速迁移的通道,有效提高聚阴离子材料的电导率,而二氧化钛则提升包覆层的结构完整性和机械稳定性,并隔离正极材料与电解液的直接接触,抑制副反应,提高界面稳定性,从而有效解决聚阴离子钠离子正极材料电导率低的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the field of sodium ion battery positive electrode materials, and particularly discloses a polyanion type sodium ion battery positive electrode material and a preparation method thereof. The polyanion type sodium ion battery positive electrode material comprises polyanion positive electrode material particles and a titanium dioxide / carbon fiber composite layer wrapped on the surfaces of the polyanion positive electrode material particles, the titanium dioxide / carbon fiber composite layer is prepared from raw materials containing n-butyl titanate and acidified carbon nanofiber powder through dissolution-gelation, drying and inert atmosphere sintering. The polyanion type sodium ion battery positive electrode material has the advantages of fast sodium ion diffusion speed, high conductivity, excellent rate performance and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of sodium-ion battery cathode materials technology, and more specifically, it relates to a polyanionic sodium-ion battery cathode material and its preparation method. Background Technology

[0002] With the development of the new energy industry, the demand for energy storage is particularly strong. Given the important role of rechargeable batteries in large-scale energy storage, and their significant advantages in stability, cost of use, and environmental friendliness, they have become the first choice.

[0003] Among existing rechargeable batteries, lithium / sodium-ion batteries have gradually become the main type, especially lithium-ion batteries, whose research is quite mature. However, the uneven distribution and insufficient reserves of lithium resources prevent them from meeting the requirements of large-scale energy storage. Sodium-ion batteries, due to their abundant sodium resources, low cost, and environmental friendliness, are considered the main competitors for next-generation new energy batteries.

[0004] Sodium-ion battery cathode materials mainly fall into three categories: layered oxides, polyanionic compounds, and Prussian blue compounds. While layered oxides offer high specific capacity, their irreversible phase transitions and transition metal dissolution caused by deep desodiuming severely limit cycle stability. Prussian blue compounds, on the other hand, exhibit dissolution of transition metal ions, and their water of crystallization is difficult to remove, leading to gas generation at high potentials. Polyanionic sodium-ion battery cathode materials are widely considered the most promising cathode materials for sodium-ion batteries due to their excellent structural stability, small volume changes during charge and discharge, high voltage plateau, and high energy density. However, polyanionic cathode materials generally suffer from low conductivity, resulting in slow electrochemical reactions that severely affect their electrochemical performance, limiting their rate performance and cycle life. Therefore, developing high-performance polyanionic sodium-ion battery cathode materials is crucial. Summary of the Invention

[0005] To improve the electron and ion transport of polyanionic cathode materials and enhance cycle stability and rate performance, this application provides a polyanionic sodium-ion battery cathode material and its preparation method.

[0006] In a first aspect, this application provides a polyanionic sodium-ion battery cathode material, employing the following technical solution: A polyanionic sodium-ion battery cathode material includes polyanionic cathode material particles and a titanium dioxide / carbon fiber composite layer coated on the surface of the polyanionic cathode material particles. The titanium dioxide / carbon fiber composite layer is made from raw materials containing tetrabutyl titanate and acidified carbon nanofiber powder through dissolution-gelation, drying, and inert atmosphere sintering.

[0007] By adopting the above technical solution, the carbon fiber powder is acidified, which increases the content of oxygen-containing functional groups on the surface of the carbon fiber, making it easier to disperse in the liquid medium. After gelation, tetrabutyl titanate can form a titanium dioxide precursor sol. After being mixed with acidified carbon nanofiber powder, it is sintered under an inert atmosphere. The titanium dioxide precursor sol is further dehydrated and crystallized, forming a nano-titanium dioxide layer on the surface of the polyanion cathode material particles. Meanwhile, the acidified carbon nanofiber powder constructs a conductive framework structure on the surface of the polyanion cathode material particles. Therefore, a composite coating layer composed of interwoven titanium dioxide nanoparticles and carbon fibers can be constructed on the surface of the polyanion cathode material particles.

[0008] The acidified carbon nanofiber powder coated on the surface of polyanion cathode material particles is interconnected between particles to form a continuous three-dimensional conductive framework, providing a channel for rapid electron migration. This effectively overcomes the inherent defect of extremely low electronic conductivity in polyanion sodium-ion battery cathode materials. Titanium dioxide, as part of the composite coating layer, can physically isolate the cathode material from direct contact with the electrolyte, suppress side reactions, prevent the loss of active materials during cycling, maintain the long-term stability of the internal conductive network, and stabilize the electrode / electrolyte interface. Furthermore, the combination of titanium dioxide and carbon fiber can improve the structural integrity and mechanical stability of the coating layer, ensuring that the carbon fiber conductive network is not damaged. In addition, titanium dioxide can also be doped to improve the intrinsic electronic conductivity of polyanion cathode materials.

[0009] Preferably, the mass ratio of the titanate n-butyl ester to the acidified carbon nanofiber powder is 1:1-2.

[0010] By adopting the above technical solution, the titanate n-butyl ester and acidified carbon nanofiber powder in the above ratio can ensure that titanium dioxide is uniformly and firmly coated on the surface of acidified carbon fiber and polyanion cathode material particles, forming a stable composite layer and constructing a highly efficient conductive network to improve conductivity. If there is too little acidified carbon nanofiber powder, the titanium dioxide coating layer may be too thick or uneven, which is prone to cracking or falling off during charging and discharging. The composite layer is unstable, and the formed conductive network is insufficient, the electron transport path is blocked, and the overall conductivity cannot be effectively improved. On the other hand, if too much acidified carbon nanofiber powder is used, a continuous and complete titanium dioxide coating layer cannot be formed, causing some cathode material particles to be directly exposed in the electrolyte, weakening the protective effect. At the same time, although the conductive network is more complete, it will affect the proportion of polyanion cathode material particles in the electrode material, reducing the overall energy density of the battery.

[0011] Preferably, the raw materials of the titanium dioxide / carbon fiber composite layer also include poloxamer and a carbon source. The amount of poloxamer is 0.1-1 wt% of the total amount of titanate n-butyl ester and acidified carbon nanofiber powder, and the amount of carbon source is 0.5-1.5 wt% of the total amount of titanate n-butyl ester and acidified carbon nanofiber powder.

[0012] By employing the above technical solution, poloxamer and a carbon source are added to the raw materials for preparing the composite layer. Poloxamer is an amphiphilic molecule that can self-assemble into micelles in solution. The hydrolysis products of tetrabutyl titanate arrange around these micelles. During high-temperature calcination, the uniform mesopores left by the decomposition of poloxamer enable precise control of the pore structure of the titanium dioxide layer. Moreover, poloxamer can prevent the agglomeration of acidified carbon nanofiber powder through steric hindrance, ensuring its uniform dispersion and thus constructing a uniform three-dimensional conductive network. The carbon source, through pyrolysis at high temperature, forms an amorphous carbon layer, acting as a binder to more tightly bond the dispersed acidified carbon nanofiber powder and cathode material particles, strengthening the conductive network and supplementing the coating of cathode material particles to form a more comprehensive conductive layer.

[0013] Poloxamer decomposes at high temperatures, acting as a soft template and pore-forming agent, leaving numerous uniform mesopores in the composite layer. The carbon source, as a coating precursor, pyrolyzes at high temperatures to form a conductive amorphous carbon layer, tightly wrapping the surface of the cathode material particles. This fills the gaps caused by the disruption of the conductive pathway due to the destruction of the carbon fiber conductive network caused by poloxamer pore formation, ensuring rapid electron conduction. At the same time, the formation of amorphous carbon increases the bonding tightness between the composite layer and the cathode material particles. The mesoporous structure formed by poloxamer provides a fast channel for electrolyte penetration and sodium ion migration, reducing the ion diffusion resistance brought by the carbon layer. Therefore, the electron and ion transport efficiency is improved simultaneously, enhancing rate performance. Moreover, the mesoporous structure effectively buffers volume changes during charge and discharge, while the amorphous carbon layer suppresses side reactions, reduces the contact between the cathode material and the electrolyte, and improves long-term cycle stability.

[0014] Preferably, the carbon source is selected from at least one of citric acid, glucose, oxalic acid, ascorbic acid, sucrose, and polyethylene glycol.

[0015] Preferably, the acidified carbon nanofiber powder is prepared by impregnating phosphorus-doped porous carbon nanofibers with nitric acid solution, heat-treating them at 130-140°C, washing them until neutral, drying them, and grinding them into powder.

[0016] By adopting the above technical solutions, phosphorus doping can increase the interlayer spacing of carbon layers, providing a wider transport channel for sodium ions, significantly reducing the resistance to their insertion and extraction. In addition, the phosphorus doping process forms abundant macropore, mesopore and micropore structures, shortening the diffusion distance of sodium ions and providing more active sites for sodium storage, thereby improving the rate performance of the cathode material.

[0017] Preferably, the polyanionic cathode material particles are at least one of Na3V2O2(PO4)2F, Na3V2(PO4)3, Na3Fe2(PO4)(P2O7), Na2FeP2O7, Na4Fe3(PO4)2(P2O7) and Na3V2(PO4)2F3.

[0018] Secondly, this application provides a method for preparing a polyanionic sodium-ion battery cathode material, employing the following technical solution: A method for preparing a polyanionic sodium-ion battery cathode material includes the following steps: The sodium source, transition metal source and anion source are mixed evenly to obtain a preliminary mixture; The initial mixture was mixed with PVP, PEO and deionized water, spray dried, and pre-calcined at 330-350℃ for 5-6 hours under an argon atmosphere to obtain precursor powder. Tetrabutyl titanate was dispersed in ethanol, stirred at 80-90℃ for 1-2 hours, and then acidified carbon nanofiber powder was added. After ultrasonic dispersion for 2-4 hours, it was mixed with precursor powder and stirred continuously at room temperature for 4-5 hours. After drying, it was sintered in an argon atmosphere to obtain polyanionic sodium-ion battery cathode material.

[0019] By employing the above technical solution, a preliminary mixture prepared by mixing sodium source, transition metal source, and anion source is mixed with an aqueous solution of PVP (polyvinylpyrrolidone) and PEO (polyethylene oxide). A homogeneous precursor powder is rapidly obtained through spray drying. During pre-calcination at 330-350℃, PVP / PEO partially decomposes, not only initially fixing the porous structure of the precursor but also achieving preliminary in-situ carbon coating. Then, tetrabutyl titanate is dispersed in an ethanol solution, and the sol-gel method is used to hydrolyze the tetrabutyl titanate in ethanol to form carbon dioxide. Titanium precursor sol is prepared, and then acidified carbon nanofiber powder is added as a framework to guide the titanium dioxide precursor to adhere uniformly to its surface. The mixture is then mixed with the precursor powder and dried to form a uniform titanium dioxide / carbon fiber composite precursor coating layer on the surface of the precursor powder particles. Subsequently, the mixture is sintered at high temperature in an argon atmosphere. The precursor reacts to generate the target polyanionic material, while the organic components in PVP / PEO and tetrabutyl titanate are carbonized to form a conductive carbon layer. This results in a core-shell structure with porous polyanionic cathode material particles inside and a titanium dioxide / carbon fiber composite layer on the surface.

[0020] PVP and PEO, as surfactants, increase slurry viscosity, which is beneficial for forming spherical or near-spherical secondary particles during spray drying and creating a rich porous structure. This increases the contact area between the electrode and the electrolyte, effectively buffering volume changes during charging and discharging, and improving structural stability. During subsequent sintering, PVP and PEO undergo thermal decomposition, with carbon elements deposited in situ on the material surface, forming a uniform and dense conductive carbon layer. PVP is also rich in nitrogen, and in situ nitrogen doping occurs during pyrolysis, further enhancing the electronic conductivity of the material. In addition, the different thermal decomposition temperatures of PVP and PEO help to build a gradient pore structure within the material. During coating and sintering, the carbon skeleton produced by their decomposition provides structural support, preventing the collapse and aggregation of precursor particles, thus maintaining the porous and spherical morphology of the polyanionic material. Furthermore, PVP and PEO contribute to the good uniformity and stability of the initial mixture, preventing sedimentation and ensuring good spray processing performance.

[0021] Preferably, the total amount of the tetrabutyl titanate and the acidified carbon nanofiber powder is 3-5 wt% of the total weight of the initial mixture.

[0022] By adopting the above technical solution, the above-mentioned amounts of tetrabutyl titanate and acidified carbon nanofiber powder can construct a highly efficient three-dimensional conductive network on the surface of the cathode particles, providing a channel for electron transport, significantly improving the conductivity of the polyanionic cathode material, and simultaneously physically isolating the cathode material particles from the electrolyte to prevent unnecessary side reactions. This helps maintain the stability of the material structure during charging and discharging, and extends the cycle life of the battery. If the amount of tetrabutyl titanate and acidified carbon nanofiber powder is too small, the formed conductive network will be discontinuous, and the improvement on electronic conductivity will be limited.

[0023] Preferably, the total mass of PVP and PEO is 5-10 wt% of the initial mixture, and the mass ratio of PVP to PEO is 1-3:1.

[0024] By adopting the above technical solution, an appropriate amount of polymer can prevent precursor particles from agglomerating, ensure the uniformity of the slurry, and form an ideal porous structure. The carbon layer formed after pyrolysis can improve conductivity. However, excessive addition will lead to too many pores, collapse of the porous structure, or reduced tap density. Excessive slurry viscosity during spray drying will affect the effect. Too much or too little will result in poor dispersion of precursor particles.

[0025] Preferably, the sintering temperature is 650-800℃, the heating rate is 5-10℃ / min, and the holding time during sintering is 8-10h.

[0026] Preferably, the sodium source is selected from at least one of sodium metaphosphate, sodium carbonate, sodium sulfate, sodium chloride, and sodium oxalate; the transition metal source is an iron source, a V source, a Mn source, or a Cr source; the iron source is at least one of iron powder, iron oxide, ferric nitrate nonahydrate, ferric chloride, and ferric sulfate; the V source is vanadium oxide or ammonium metavanadate; the Mn source is selected from at least one of manganese oxide, manganese nitrate, and manganese chloride; the Cr source is selected from at least one of chromium oxide, sodium chromate, and chromium hydroxide; and the anion source is a Si source, a F source, a P source, or P2O7. 4- The source, Si, is at least one of sodium silicate, silicic acid, and ethyl silicate; P is at least one of phosphoric acid, sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, and ammonium dihydrogen phosphate; and F is at least one of sodium fluoride, ammonium fluoride, and hydrofluoric acid.

[0027] In summary, this application has the following beneficial effects: 1. Because this application coats the surface of polyanionic cathode material particles with a titanium dioxide / carbon fiber composite layer, and the acidified carbon nanofiber powder is interconnected between the particles to form a long-range, continuous three-dimensional conductive framework, it provides a fast migration channel for electrons, effectively improving the conductivity of the polyanionic material. Meanwhile, titanium dioxide enhances the structural integrity and mechanical stability of the coating layer, isolates the cathode material from direct contact with the electrolyte, suppresses side reactions, and improves interface stability, thereby effectively solving the problem of low conductivity of polyanionic sodium ion cathode materials.

[0028] 2. In this application, a certain amount of poloxamer and carbon source are preferably added during the preparation of the titanium dioxide / carbon fiber composite layer. Poloxamer can form an organic and inorganic hybrid structure with tetrabutyl titanate. It decomposes at high temperature under an argon atmosphere to form a large number of uniform mesopores, thereby obtaining a porous titanium dioxide / carbon fiber composite network layer with high porosity. This promotes ion transport, improves rate performance, buffers volume changes, and enhances structural stability. The addition of carbon source can repair the conductive network, ensure rapid electron conduction, enhance cycle stability, and improve rate performance.

[0029] 3. In this application, PVP and PEO are preferably added when preparing the precursor powder and spray drying is used. When preparing sodium source, anion source and transition metal source into polyanion cathode material particles, PVP and PEO can construct a gradient pore structure, which is beneficial to ion transport, improves rate performance, and effectively buffers volume changes, thereby improving structural stability. Detailed Implementation

[0030] The present application will be further described in detail below with reference to the embodiments.

[0031] Example 1: Preparation of acidified carbon nanofiber powder: 0.1 g PMMA (polymethyl methacrylate), 0.9 g PAN (polyacrylonitrile), and 2 mmol PPA (phenylphosphonic acid) were dissolved in 10 mL DMF and stirred at room temperature for 20 h. Electrospinning was then performed to obtain a fiber web. The positive voltage during electrospinning was 17 kV, the negative voltage was -2 kV, the receiving distance was 15 cm, the feeding speed was 0.085 mm / min, the spinning temperature was 25 °C, and the humidity was 25%. The fiber web was heated to 280°C at a rate of 1°C / min in a tube furnace and held for 2 hours. Then, it was heated to 800°C at a rate of 2°C / min under an argon atmosphere and held for 2 hours. After cooling to room temperature, it was ground, soaked in a 1 mol / L KOH aqueous solution for 24 hours, dried, and then heated to 800°C at a rate of 1°C / min under an argon atmosphere and held for 30 minutes. The KOH solution was then neutralized with a 1 mol / L HCl aqueous solution, washed until the pH reached 7, and dried overnight at 80°C. The dried fiber web was soaked in a 35wt% nitric acid solution for 24 hours with a solid-liquid ratio of 1g:10mL. After filtration, the fiber web was heat-treated at 140℃ for 6 hours, then washed with deionized water until the pH reached 7. After drying at 80℃ for 12 hours and grinding into powder, acidified carbon nanofiber powder with a particle size of 50nm was obtained.

[0032] Example

[0033] This application involves various types of polyanionic cathode material particles. To effectively illustrate the technical effects of this application, Na3V2O2(PO4)2F, Na3V2(PO4)3, and Na3Fe2(PO4)(P2O7) are selected for comparison. However, the selection of material types in this embodiment is not a limitation on the polyanionic cathode material particles. In this application, PVP is selected from BASF, model LUVITEC K30, PEO is selected from Wuhan Kemike Biopharmaceutical, model KMK, and the carbon fiber length is 3mm, selected from Jiangxi Shuobang New Materials.

[0034] Example 1: A polyanionic sodium-ion battery cathode material, comprising polyanionic cathode material particles and a titanium dioxide / carbon fiber composite layer coated on the surface of the polyanionic cathode material particles, wherein the polyanionic cathode material particles are Na3V2(PO4)3; the raw material of the titanium dioxide / carbon fiber composite layer comprises tetrabutyl titanate and acidified carbon nanofiber powder in a mass ratio of 1:2, and the acidified carbon nanofiber powder is prepared by the following method: commercially available carbon fibers are soaked in a 35wt% nitric acid solution for 24h, filtered, heat-treated at 140℃ for 6h, washed with deionized water until pH is 7, dried at 80℃ for 12h, and ground into powder to obtain acidified carbon nanofiber powder with a particle size of 50nm.

[0035] The preparation method of this polyanionic sodium-ion battery cathode material includes the following steps: S1. Mix vanadium pentoxide and sodium metaphosphate at a mass ratio of 1:1.1, ball mill for 20 minutes, and mix evenly to obtain a preliminary mixture; S2. The initial mixture is mixed with PVP, PEO and 100 mL of deionized water, spray-dried, and then pre-calcined at 350 °C for 5 h at a rate of 5 °C / min under an argon atmosphere to obtain precursor powder. The mass ratio of PVP to PEO is 2:1, and the total mass of PVP and PEO is 10 wt% of the mass of the initial mixture. S3. Disperse tetrabutyl titanate in 50 mL of ethanol, stir at 80 °C for 2 h, add acidified carbon nanofiber powder, sonicate at 250 W for 4 h, mix with precursor powder, stir continuously at room temperature for 4 h, dry at 80 °C, heat to 650 °C at 5 °C / min under argon atmosphere, and hold for 8 h. The amount of tetrabutyl titanate and acidified carbon nanofiber powder is 5 wt% of the total mass of the initial mixture.

[0036] Example 2: A polyanionic sodium-ion battery cathode material, comprising polyanionic cathode material particles and a titanium dioxide / carbon fiber composite layer coated on the surface of the polyanionic cathode material particles, wherein the polyanionic cathode material particles are Na3V2(PO4)3; the raw material of the titanium dioxide / carbon fiber composite layer comprises tetrabutyl titanate and acidified carbon nanofiber powder in a mass ratio of 1:1, and the acidified carbon nanofiber powder is prepared by the following method: commercially available carbon fibers are soaked in a 35wt% nitric acid solution for 24h, filtered, heat-treated at 140℃ for 6h, washed with deionized water until pH is 7, dried at 80℃ for 12h, and ground into powder to obtain acidified carbon nanofiber powder with a particle size of 50nm.

[0037] The preparation method of the above-mentioned polyanionic sodium-ion battery cathode material includes the following steps: S1. Mix vanadium pentoxide and sodium metaphosphate at a mass ratio of 1:1.1, ball mill for 20 minutes, and mix evenly to obtain a preliminary mixture; S2. The initial mixture was mixed with PVP, PEO and 20 mL of deionized water, spray-dried, and then pre-calcined at 330 °C for 6 h at a rate of 5 °C / min under an argon atmosphere to obtain precursor powder. The mass ratio of PVP to PEO was 3:1, and the total mass of PVP and PEO was 5 wt% of the mass of the initial mixture. S3. Disperse tetrabutyl titanate in 50 mL of ethanol, stir at 90 °C for 1 h, add acidified carbon nanofiber powder, sonicate at 250 W for 2 h, mix with precursor powder, stir continuously at room temperature for 5 h, dry at 80 °C, heat to 750 °C at 10 °C / min under argon atmosphere, and hold for 10 h. The amount of tetrabutyl titanate and acidified carbon nanofiber powder is 3 wt% of the initial mixture.

[0038] Example 3: A polyanionic sodium-ion battery cathode material, comprising polyanionic cathode material particles and a titanium dioxide / carbon fiber composite layer coated on the surface of the polyanionic cathode material particles, wherein the polyanionic cathode material particles are Na3V2(PO4)3; the raw material of the titanium dioxide / carbon fiber composite layer comprises tetrabutyl titanate and acidified carbon nanofiber powder in a mass ratio of 1:1.5, and the acidified carbon nanofiber powder is prepared by the following method: commercially available carbon fibers are soaked in a 35wt% nitric acid solution for 24h, filtered, heat-treated at 140℃ for 6h, washed with deionized water until pH is 7, dried at 80℃ for 12h, and ground into powder to obtain acidified carbon nanofiber powder with a particle size of 50nm.

[0039] The preparation method of the above-mentioned polyanionic sodium-ion battery cathode material includes the following steps: S1. Mix vanadium pentoxide and sodium metaphosphate at a mass ratio of 1:1.1, ball mill for 20 minutes, and mix evenly to obtain a preliminary mixture; S2. The initial mixture was mixed with PVP, PEO and 20 mL of deionized water, spray-dried, and then pre-calcined at 350 °C for 6 h at a rate of 5 °C / min under an argon atmosphere to obtain precursor powder. The mass ratio of PVP to PEO was 1:1, and the total mass of PVP and PEO was 8 wt% of the mass of the initial mixture. S3. Disperse tetrabutyl titanate in 50 mL of ethanol, stir at 80 °C for 1 h, add acidified carbon nanofiber powder, sonicate at 250 W for 3 h, mix with precursor powder, stir continuously at room temperature for 5 h, dry at 80 °C, heat to 800 °C at 8 °C / min under argon atmosphere, and hold for 8 h. The amount of tetrabutyl titanate and acidified carbon nanofiber powder is 4 wt% of the total mass of the initial mixture.

[0040] Example 4: A polyanionic sodium-ion battery cathode material, which differs from Example 1 in that the acidified carbon nanofiber powder is prepared in Example 1.

[0041] Example 5: A polyanionic sodium-ion battery cathode material, differing from Example 4 in that poloxamer and a carbon source are added to the titanium dioxide / carbon fiber composite layer. The carbon source is glucose. Step S3 specifically involves: dispersing tetrabutyl titanate in 50 mL of ethanol, stirring at 80°C for 2 h, adding acidified carbon nanofiber powder, poloxamer, and glucose, ultrasonicating at 250 W for 4 h, mixing with precursor powder, stirring continuously at room temperature for 4 h, drying at 80°C, heating to 650°C at 5°C / min under an argon atmosphere, and holding at that temperature for 8 h. The amount of tetrabutyl titanate and acidified carbon nanofiber powder is 5 wt% of the total mass of the initial mixture, while the amount of poloxamer is 1 wt% of the total weight of tetrabutyl titanate and acidified carbon nanofiber powder, and the carbon source is 1.5 wt% of the total weight of tetrabutyl titanate and acidified carbon nanofiber powder.

[0042] Example 6: A polyanionic sodium-ion battery cathode material, differing from Example 4 in that poloxamer is added to the titanium dioxide / carbon fiber composite layer. Step S3 specifically involves: dispersing tetrabutyl titanate in 50 mL of ethanol, stirring at 80°C for 2 h, adding acidified carbon nanofiber powder and poloxamer, ultrasonicating at 250 W for 4 h, mixing with precursor powder, stirring continuously at room temperature for 4 h, drying at 80°C, heating to 650°C at 5°C / min under an argon atmosphere, and holding at that temperature for 8 h. The amount of tetrabutyl titanate and acidified carbon nanofiber powder is 5 wt% of the total mass of the initial mixture, while the amount of poloxamer is 1 wt% of the total weight of tetrabutyl titanate and acidified carbon nanofiber powder.

[0043] Example 7: A polyanionic sodium-ion battery cathode material, comprising polyanionic cathode material particles and a titanium dioxide / carbon fiber composite layer coated on the surface of the polyanionic cathode material particles, wherein the polyanionic cathode material particles are Na3Fe2(PO4)(P2O7); the raw material of the titanium dioxide / carbon fiber composite layer comprises tetrabutyl titanate and acidified carbon nanofiber powder in a mass ratio of 1:2, and the acidified carbon nanofiber powder is prepared by the following method: commercially available carbon fibers are soaked in a 35wt% nitric acid solution for 24h, filtered, heat-treated at 140℃ for 6h, washed with deionized water until pH is 7, dried at 80℃ for 12h, and ground into powder to obtain acidified carbon nanofiber powder with a particle size of 50nm.

[0044] The preparation method of this polyanionic sodium-ion battery cathode material includes the following steps: S1. Mix 1.616g of ferric nitrate nonahydrate and 0.936g of sodium dihydrogen phosphate, add 21mL of isopropanol, ball mill at 450r / min for 6h, and then vacuum dry at 80℃ for 2h to obtain the initial mixture. S2. The initial mixture is mixed with PVP, PEO and 100 mL of deionized water, spray-dried, and then pre-calcined at 350 °C for 5 h at a rate of 5 °C / min under an argon atmosphere to obtain precursor powder. The mass ratio of PVP to PEO is 2:1, and the total mass of PVP and PEO is 10 wt% of the mass of the initial mixture. S3. Disperse tetrabutyl titanate in 50 mL of ethanol, stir at 80 °C for 2 h, add acidified carbon nanofiber powder, sonicate at 250 W for 4 h, mix with precursor powder, stir continuously at room temperature for 4 h, dry at 80 °C, heat to 650 °C at 5 °C / min under argon atmosphere, and hold for 8 h. The amount of tetrabutyl titanate and acidified carbon nanofiber powder is 5 wt% of the total mass of the initial mixture.

[0045] Example 8: A polyanionic sodium-ion battery cathode material, comprising polyanionic cathode material particles and a titanium dioxide / carbon fiber composite layer coated on the surface of the polyanionic cathode material particles, wherein the polyanionic cathode material particles are Na3V2O2(PO4)2F; the raw material of the titanium dioxide / carbon fiber composite layer comprises tetrabutyl titanate and acidified carbon nanofiber powder in a mass ratio of 1:2, and the acidified carbon nanofiber powder is prepared by the following method: commercially available carbon fibers are soaked in a 35wt% nitric acid solution for 24h, filtered, heat-treated at 140℃ for 6h, washed with deionized water until pH is 7, dried at 80℃ for 12h, and ground into powder to obtain acidified carbon nanofiber powder with a particle size of 50nm.

[0046] The preparation method of the above-mentioned polyanionic sodium-ion battery cathode material includes the following steps: S1. Vanadium pentoxide and anhydrous oxalic acid in a molar ratio of 1:3 were added to a 60 mL mixture made of deionized water and ethanol in a volume ratio of 1:1. The mixture was stirred at 80 °C for 30 min. Ammonium dihydrogen phosphate, sodium carbonate and sodium fluoride were added. The mixture was stirred for another 24 h. The mixture was repeatedly centrifuged and washed with ethanol and deionized water. It was then vacuum dried overnight to obtain a preliminary mixture. The molar ratio of ammonium dihydrogen phosphate, sodium carbonate, sodium fluoride and vanadium pentoxide was 2:1:1:1. S2. The initial mixture is mixed with PVP, PEO and 100 mL of deionized water, spray-dried, and then pre-calcined at 350 °C for 5 h at a rate of 5 °C / min under an argon atmosphere to obtain precursor powder. The mass ratio of PVP to PEO is 2:1, and the total mass of PVP and PEO is 10 wt% of the mass of the initial mixture. S3. Disperse tetrabutyl titanate in 50 mL of ethanol, stir at 80 °C for 2 h, add acidified carbon nanofiber powder, sonicate at 250 W for 4 h, mix with precursor powder, stir continuously at room temperature for 4 h, dry at 80 °C, heat to 650 °C at 5 °C / min under argon atmosphere, and hold for 8 h. The amount of tetrabutyl titanate and acidified carbon nanofiber powder is 5 wt% of the total mass of the initial mixture.

[0047] Comparative Example

[0048] Comparative Example 1: A polyanionic sodium-ion battery cathode material, which differs from Example 1 in that, in step S2, PVP and PEO are not added, and it is directly spray-dried, that is: the initial mixture is mixed with 100 mL of deionized water, spray-dried, and then pre-calcined at 350 °C for 5 h at a rate of 5 °C / min under an argon atmosphere to obtain precursor powder.

[0049] Comparative Example 2: A polyanionic sodium-ion battery cathode material, which differs from Example 1 in that, in step S2, the initial mixture is mixed with PVP and 100 mL of deionized water, spray-dried, and then pre-calcined at 350 °C for 5 h at a rate of 5 °C / min under an argon atmosphere to obtain precursor powder, wherein the mass of PVP is 10 wt% of the mass of the initial mixture.

[0050] Comparative Example 3: A polyanionic sodium-ion battery cathode material, which differs from Example 1 in that, in step S3, no tetrabutyl titanate was added, i.e.: S3, acidified carbon nanofiber powder is mixed in 50 mL of ethanol, ultrasonicated at 250 W for 4 h, then mixed with precursor powder, stirred continuously at room temperature for 4 h, dried at 80 °C, heated to 650 °C at 5 °C / min under argon atmosphere, and held at that temperature for 8 h. The amount of acidified carbon nanofiber powder used is 5 wt% of the total mass of vanadium pentoxide and sodium metaphosphate.

[0051] Comparative Example 4: A polyanionic sodium-ion battery cathode material, which differs from Example 1 in that, in step S3, acidified carbon fiber powder was not added, that is: S3, tetrabutyl titanate is dispersed in 50 mL of ethanol, mixed with precursor powder, stirred continuously at room temperature for 4 h, dried at 80 °C, heated to 650 °C at 5 °C / min under argon atmosphere, and held at that temperature for 8 h, the amount of tetrabutyl titanate used is 5 wt% of the total mass of vanadium pentoxide and sodium metaphosphate.

[0052] Comparative Example 5: A polyanionic sodium-ion battery cathode material, which differs from Example 1 in that the carbon nanofiber powder is not acidified, and commercially available carbon fibers are ground into powder to obtain carbon nanofiber powder with a particle size of 50nm.

[0053] Performance testing

[0054] The polyanionic sodium-ion battery cathode material, acetylene black, and PVDF prepared in the examples and comparative examples were mixed in a mass ratio of 8:1:1 to form a slurry. The black slurry was then coated onto aluminum foil using a 120 μm four-sided coating tool. The film was then dried in a vacuum drying oven at 120°C for 6 hours. The electrode film was then punched into a disc with a radius of 12 mm using a die-cutting machine, with an active material loading of approximately 2.0 mg / cm³. 2 Using sodium metal as the counter electrode, 1 mol / L NaClO4 + solvent EC (ethylene carbonate) and DEC (1:1 vol%) + 5% FEC (fluoroethylene carbonate) as the electrolyte, and glass fiber as the separator, a CR2016 type button cell was assembled in a glove box. The electrochemical performance was tested. Ten samples were tested for each example or comparative example, and the average value of the test results was taken. The results are recorded in Table 1.

[0055] Table 1

[0056]

[0057] As can be seen from the data comparison in Table 1, the polyanionic sodium ion cathode materials prepared by the raw material amounts in Examples 1-3 have strong conductivity, good rate performance and cycle stability.

[0058] In Example 4, the acidified carbon nanofiber powder prepared in Preparation Example 1 was used. Compared with Example 1, the acidified carbon nanofiber powder was prepared in Preparation Example 1, wherein the carbon fiber is phosphorus-doped porous carbon nanofiber, which shows that the sodium ion transport speed is faster and the rate performance is higher.

[0059] Compared to Example 4, Example 5 also used poloxamer and a carbon source in the titanium dioxide / carbon fiber composite layer. As can be seen from the data in Table 1, the polyanionic sodium-ion battery cathode material prepared in Example 5 has higher rate performance and charge / discharge response rate.

[0060] Compared to Example 4, Example 6 only added poloxamer to the titanium dioxide / carbon fiber composite layer. The rate performance of the polyanionic sodium-ion battery cathode material prepared in Example 6 was improved compared to Example 4, but its cycle stability was worse and its service life was poor. This shows that adding poloxamer alone can improve the mesoporous structure, increase sodium ion migration channels, reduce sodium ion diffusion resistance, and improve rate performance, but it can also lead to the destruction of the conductive network, causing the interruption of the conductive path and affecting long-term cycle stability.

[0061] In Example 7, Na3Fe2(PO4)(P2O7) was used as polyanion cathode material particles, and in Example 8, Na3V2O2(PO4)2F was used as polyanion cathode material particles. Compared with Example 1, Examples 7 and 8 used different types of polyanion cathode material particles. The cathode materials prepared in Examples 7 and 8 also have high rate performance and long-term cycle stability.

[0062] Compared with Example 1, Comparative Example 1 did not add PVP and PEO, while Comparative Example 2 used PVP to replace PEO. The first-cycle capacity of the polyanionic sodium-ion battery cathode material prepared by Comparative Example 1 decreased and the rate performance was reduced. Although the rate performance of the polyanionic sodium-ion battery cathode material prepared by Comparative Example 2 was improved compared with Comparative Example 1, it was still not as good as Example 1. This shows that PVP and PEO can be used in combination to form a gradient pore structure inside the material and improve the ion transport speed.

[0063] In Comparative Example 3, no tetrabutyl titanate was added. Compared with Example 1, the polyanionic sodium-ion battery cathode material prepared in Comparative Example 3 showed a significant decrease in cycle stability and capacity retention.

[0064] Compared with Example 1, Comparative Example 4 did not add acidified carbon fiber powder, while Comparative Example 5 did not acidify the carbon fiber. As can be seen from the data comparison in Table 1, the conductivity and cycle life of the polyanionic sodium-ion battery cathode materials prepared in Comparative Example 4 and Comparative Example 5 decreased. It can be seen that the composite layer formed by combining acidified carbon nanofiber powder and titanium dioxide can significantly improve conductivity and interface stability.

[0065] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A polyanionic sodium-ion battery cathode material, characterized in that, It includes polyanionic cathode material particles and a titanium dioxide / carbon fiber composite layer coated on the surface of the polyanionic cathode material particles. The titanium dioxide / carbon fiber composite layer is made from raw materials containing tetrabutyl titanate and acidified carbon nanofiber powder through dissolution-gelation, drying, and inert atmosphere sintering.

2. The polyanionic sodium-ion battery cathode material according to claim 1, characterized in that: The mass ratio of the titanate n-butyl ester to the acidified carbon nanofiber powder is 1:1-2.

3. The polyanionic sodium-ion battery cathode material according to claim 1, characterized in that: The raw materials for the titanium dioxide / carbon fiber composite layer also include poloxamer and a carbon source. The amount of poloxamer is 0.1-1 wt% of the total amount of tetrabutyl titanate and acidified carbon nanofiber powder, and the amount of carbon source is 0.5-1.5 wt% of the total amount of tetrabutyl titanate and acidified carbon nanofiber powder.

4. The polyanionic sodium-ion battery cathode material according to claim 3, characterized in that: The carbon source is selected from at least one of citric acid, glucose, oxalic acid, ascorbic acid, sucrose, and polyethylene glycol.

5. The polyanionic sodium-ion battery cathode material according to claim 1, characterized in that: The acidified carbon nanofiber powder is prepared by impregnating phosphorus-doped porous carbon nanofibers with nitric acid solution, heat-treating them at 130-140℃, washing them until neutral, drying them, and grinding them into powder.

6. The polyanionic sodium-ion battery cathode material according to claim 1, characterized in that: The polyanionic cathode material particles are at least one of Na3V2O2(PO4)2F, Na3V2(PO4)3, Na3Fe2(PO4)(P2O7), Na2FeP2O7, Na4Fe3(PO4)2(P2O7) and Na3V2(PO4)2F3.

7. The method for preparing the polyanionic sodium-ion battery cathode material according to any one of claims 1-6, characterized in that, Includes the following steps: The sodium source, transition metal source and anion source are mixed evenly to obtain a preliminary mixture; The initial mixture was mixed with PVP, PEO and deionized water, spray-dried, and pre-calcined at 330-350℃ for 5-6 hours under an argon atmosphere to obtain precursor powder. Tetrabutyl titanate was dispersed in ethanol, stirred at 80-90℃ for 1-2 hours, and then acidified carbon nanofiber powder was added. After ultrasonic dispersion for 2-4 hours, it was mixed with precursor powder and stirred continuously at room temperature for 4-5 hours. After drying, it was sintered in an argon atmosphere to obtain polyanionic sodium-ion battery cathode material.

8. The method for preparing the polyanionic sodium-ion battery cathode material according to claim 7, characterized in that: The total amount of the titanate n-butyl ester and acidified carbon nanofiber powder is 3-5 wt% of the total weight of the initial mixture.

9. The method for preparing the polyanionic sodium-ion battery cathode material according to claim 7, characterized in that, The total mass of PVP and PEO is 5-10 wt% of the initial mixture, and the mass ratio of PVP to PEO is 1-3:

1.

10. The method for preparing the polyanionic sodium-ion battery cathode material according to claim 7, characterized in that, The sintering temperature under an argon atmosphere is 650-800℃, the heating rate is 5-10℃ / min, and the holding time during sintering is 8-10h.